2013
DOI: 10.1371/journal.pntd.0002151
|View full text |Cite|
|
Sign up to set email alerts
|

A Potential Role for the Interaction of Wolbachia Surface Proteins with the Brugia malayi Glycolytic Enzymes and Cytoskeleton in Maintenance of Endosymbiosis

Abstract: The human filarial parasite Brugia malayi harbors an endosymbiotic bacterium of the genus Wolbachia. The Wolbachia represent an attractive target for the control of filarial induced disease as elimination of the bacteria affects molting, reproduction and survival of the worms. The molecular basis for the symbiotic relationship between Wolbachia and their filarial hosts has yet to be elucidated. To identify proteins involved in this process, we focused on the Wolbachia surface proteins (WSPs), which are known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 78 publications
3
50
0
Order By: Relevance
“…Wolbachia is an obligate intracellular Gram-negative microorganism, maternally inherited in a wide range of arthropods, naturally present in 40% of known insect species [48]. Wolbachia is able to play the roles of parasite or of symbiont, with a preference for gonadal tissue cells, and.…”
Section: Introductionmentioning
confidence: 99%
“…Wolbachia is an obligate intracellular Gram-negative microorganism, maternally inherited in a wide range of arthropods, naturally present in 40% of known insect species [48]. Wolbachia is able to play the roles of parasite or of symbiont, with a preference for gonadal tissue cells, and.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the remarkable discoveries that infected mosquitos show resistance to dengue, Chikungunya virus, yellow fever, and even malaria [5,6] create a potentially cheap and sustainable system in which the great pandemic of Wolbachia can be used to control mosquito and other insect vectors. Equally exciting are areas that have focused on the mutualistic role that Wolbachia play with filarial nematodes, the causative agents of lymphatic filariasis and river blindness that afflict hundreds of millions of people [7,8]. This research aims to eliminate the Wolbachia infection and thereby reduce the fitness of the nematodes that depend on it.…”
Section: The Great Wolbachia Pandemicmentioning
confidence: 99%
“…These phenotypes serve to increase the frequency of infected females in a host population and therefore the scale of maternal transmission of Wolbachia to the next generation. While each of these modifications has been characterized at a foundational level, their underlying mechanisms are enigmatic [7]. …”
Section: How Did Wolbachia Spread Worldwide?mentioning
confidence: 99%
See 1 more Smart Citation
“…Melnikow et al. (2013) showed that WSP family proteins might be involved in optimization of the energy production pathway as well as in anchoring Wolbachia to the host's cytoskeleton. The hypothesis entails that pupae represent the most receptive stage for horizontal infections, which can be tested as the (trans)infection probability among developmental stages (egg, larvae, early/late pupae) of potential or actual hosts.…”
Section: Discussionmentioning
confidence: 99%